Combination of biomarkers for diagnosis of acute kidney injury after cardiopulmonary bypass. (14th January 2015) - Prowle, John Richard; Calzavacca, Paolo; Licari, Elisa; Ligabo, E. Valentina; Echeverri, Jorge E.; Bagshaw, Sean M.; Haase-Fielitz, Anja; Haase, Michael; Ostland, Vaughn; Noiri, Eisei; Westerman, Mark; Devarajan, Prasad; et al.
Abstract: Novel acute kidney injury (AKI) biomarkers offer promise of earlier diagnosis and risk stratification, but have yet to find widespread clinical application. We measured urinary α and π glutathione S -transferases (α-GST and π-GST), urinaryl -type fatty acid-binding protein (l -FABP), urinary neutrophil gelatinase-associated lipocalin (NGAL), urinary hepcidin and serum cystatin c (CysC) before surgery, post-operatively and at 24 h after surgery in 93 high risk patient undergoing cardiopulmonary bypass (CPB) and assessed the ability of these biomarkers alone and in combination to predict RIFLE-R defined AKI in the first 5 post-operative days. Twenty-five patients developed AKI. π-GST (ROCAUC = 0.75), lower urine Hepcidin:Creatine ratio at 24 h (0.77), greater urine NGAL:Cr ratio post-op (0.73) and greater serum CysC at 24 h (0.72) best predicted AKI. Linear combinations with significant improvement in AUC were: Hepcidin:Cr 24 h + post-operative π-GST (AUC = 0.86, p  = 0.01), Hepcidin:Cr 24 h + NGAL:Cr post-op (0.84, p  = 0.03) and CysC 24 h + post-operative π-GST (0.83, p  = 0.03), notably these significant biomarkers combinations all involved a tubular injury and a glomerular filtration biomarker. Despite statistical significance in receiver–operator characteristic (ROC) analysis, when assessed by ability to define patients to two groups at high and low risk of AKI, combinations failed to significantly improve classification of risk compared to the best single biomarkers. In an alternative approach using Classification and Regression Tree (CART) analysis a model involving NGAL:Cr measurement post-op followed by Hepcidin:Cr at 24 h was developed which identified high, intermediate and low risk groups for AKI. Regression tree analysis has the potential produce models with greater clinical utility than single combined scores.